A VISUAL ANALYSIS OF MULTICULTURAL VALUES IN JUNIOR HIGH SCHOOL ENGLISH TEXTBOOK - Yusup, Maulana; Suryaman, Maman (IKIP Siliwangi, 2021)
The purpose of the present study is to analyze visual elements of junior high school English textbook published by the Ministry of Education and Culture of the Republic of Indonesia. The visual elements were analyzed by using the visual semiotic theory by (Barthes, 1977). This study shows that there are three categories of multicultural values represented in the EFL textbook: respecting other people’s tradition, and appreciating women’s equal rights, and appreciating other people’s perspectives. Three images represented respecting other people’s tradition, one image represented appreciating women’s equal right, and two images represented appreciating other people’s perspective. Furthermore, two visuals found in the present study are categorized as source culture (SC), four visual elements are categorized as universality culture (UC), and there is not visual elements representing target culture (TC). The present study found that there is still imbalanced representation of multicultural values in EFL textbook for Indonesian junior high school. Keywords: EFL textbook, Visual Analysis, Multicultural Values